Influência da ordem de preparo dos canais radiculares na eficiência do preparo e resistência a fadiga ciclica do sistema WaveOne Gold em molares superiores - Alberton, Carlla Sloane (2019)
This study aimed to evaluate the influence of the shaping sequence on the four root canals in upper molar and to determine if the root canal anatomy influences the cutting efficiency, instrument deformation, cyclic fatigue, and the instrumentation time of WaveOne Gold instrument Primary (25.07). Forty-eight permanent maxillary molars with four root canals were selected. Teeth were divided into four groups according to their root canal shaping sequence. Group MB-DB-P-MB2; Group DB-P-MB2-MB; Group P-MB2-MB-DB e Group MB2-MB-DB-P. Computerized microtomography was performed pre and post instrumentation to obtain the initial and final volume measurements of the teeth. The instruments were evaluated by scanning electron microscopy to verify the wear features after use. The cyclic fatigue test was also performed to evaluate the time in seconds and the number of cycles until the instrument fracture. A stainless steel device simulating the root canal with a 60° angle of curvature and a 5-mm radius of curvature was used. The shaping time was recorded. KruskalWallis and Dunn’s test were performed to analyze the volume variation and preparation time, ANOVA and Tukey test was performed to analyze the cyclic fatigue, used with a significance level of 5%. Data were analyzed statistically at 5% significance level. There were no statistically significant differences between groups in volume variation, cyclic fatigue, and the shaping time od WOG (p> 0.05). However, there is a statistically significant difference between groups for the instruments deformation, in which DB-PMB2-MB and P-MB2-MB-DB presented high deformation. In conclusion, the sequence of root canal preparation did not influence the volume variation, the cyclic fatigue resistance of the instrument, and the time of preparation of the WOG system. The preparation of the upper molar root canals should follow the following sequences MBDB-P-MB2 or MB2-MB-DB-P. The aim of this study was to evaluate the influence of the shaping order on the four root canal in upper molar and to determine if the root canal anatomy has influence on the cutting efficiency, instrument deformation, cyclic fatigue and the instrumentation time of WaveOne Gold instrument Primary. Forty-eight maxillary permanent molars with four root canals were selected. Teeth were divided into four groups according their root canal shaping sequence. Group MB-DB-P-MB2; Group DB-P-MB2-MB; Group P-MB2-MBDB e Group MB2-MB-DB-P. Computerized microtomography was performed pre and post instrumentation to obtain the initial and final volume measurements of the teeth. The instruments were evaluated by scanning electron microscopy to verify the wear features after use. The cyclic fatigue test was also performed to evaluate the time in seconds and the number of cycles until the instrument fracture. The shaping time was also recorded. There were no statistically significant differences between groups in all tested parameters (p> 0.05). In conclusion, the shaping sequence did not influence the cutting efficiency, the instrument deformation, the cyclic fatigue strength and the instrumentation time of root canals.